Penerapan Nilai-Nilai Budaya Melayu Dalam Tata Kelola Aparatur Sipil Negara di Kabupaten Lingga Sebagai Bunda Tanah Melayu Provinsi Kepulauan Riau - Muhaimin Wahyudi; Alfiandri Alfiandri; Agus Hendrayady (Student Scientific Creativity Journal, 2024)
Malay culture is one of the various cultures that live, grow and develop on this earth. The aim of this research is, among other things, to find out how the State Civil Apparatus Governance is in Realizing Malay Cultural Values in Lingga Regency, Riau Islands Province as the Mother of the Malay Land. In this research, researchers used qualitative methods, this approach uses a qualitative approach with descriptive methods. The theory used in this research uses Governance according to Widyananda (2008). The indicators in this research are Transparency, Accountability, Equitable, Responsibility. The data collection techniques used were interviews, observation and documentation. The results of this research are that the management of the State Civil Apparatus in realizing Malay cultural values cannot be said to be running well, this is because there are still many shortcomings in its management. Even though there are regulations made regarding the promotion of Malay culture in Lingga Regency, as well as there are programs created by each regional apparatus organization (OPD) regarding their management in realizing Malay cultural values. However, its implementation in ASN life is not fully carried out, because many ASN do not understand the values of Malay culture. This is also encouraged because not all ASN in Lingga Regency are Malay.